2022
DOI: 10.1093/dote/doac040
|View full text |Cite
|
Sign up to set email alerts
|

Histologic response to steroids in eosinophilic esophagitis is dependent on delivery compound

Abstract: Summary Topical steroids are commonly used in treatment of eosinophilic esophagitis (EoE), but currently there is lack of data to clarify most effective regimen. We aimed to study the achievement of histologic remission using the same dose of budesonide in two different delivery formulations. Patients with established EoE treated with pharmacy compounded budesonide capsule or budesonide Rincinol gel (both 3 mg twice daily) were studied retrospectively. Those with pre-treatment and post-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Despite the overall lower remission rates, our data suggests there is no difference in efficacy among the different delivery vehicles. An adult study demonstrated higher rates of remission using budesonide gel mixed with Rincinol gel as compared to budesonide capsules crushed into various vehicles such as Splenda, syrup, or honey 15 . This study, however, did not compare rates of remission between different vehicles used with budesonide capsules.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite the overall lower remission rates, our data suggests there is no difference in efficacy among the different delivery vehicles. An adult study demonstrated higher rates of remission using budesonide gel mixed with Rincinol gel as compared to budesonide capsules crushed into various vehicles such as Splenda, syrup, or honey 15 . This study, however, did not compare rates of remission between different vehicles used with budesonide capsules.…”
Section: Discussionmentioning
confidence: 83%
“…An adult study demonstrated higher rates of remission using budesonide gel mixed with Rincinol gel as compared to budesonide capsules crushed into various vehicles such as Splenda, syrup, or honey. 15 This study, however, did not compare rates of remission between different vehicles used with budesonide capsules. Our results are similar to other small prospective or retrospective cohort studies that showed favorable alternatives to standard OVB formulation with Splenda 8,10,11 and thus may address concerns regarding taste, cost, and possible adverse effects of consuming large amounts of sucralose.…”
Section: Discussionmentioning
confidence: 91%